Ten-year results of a single-center trial investigating heart rate control with Ivabradine or Metoprolol succinate in patients after heart transplantation - Darche, Fabrice Fernand; Alt, Alexandra C.; Rivinius, Rasmus; Helmschrott, Matthias; Ehlermann, Philipp; Frey, Norbert; Rahm, Ann-Kathrin (Journal of cardiovascular development and disease, 2025)
Aims: Sinus tachycardia after heart transplantation (HTX) due to cardiac graft denervation is associated with reduced post-transplant survival and requires adequate treatment. We analyzed the long-term effects of heart rate control with ivabradine or metoprolol succinate in HTX recipients. Methods: This observational retrospective single-center study analyzed the ten-year results of 110 patients receiving ivabradine (n = 54) or metoprolol succinate (n = 56) after HTX. Analysis included comparison of demographics, medications, heart rates, blood pressure values, echocardiographic features, cardiac catheterization data, cardiac biomarkers, and post-transplant survival including causes of death. Results: Both groups showed no significant differences concerning demographics or medications (except for ivabradine and metoprolol succinate). At 10-year follow-up, HTX recipients with ivabradine showed a significantly lower heart rate (72.7 ± 8.5 bpm) compared to baseline (88.8 ± 7.6 bpm; p < 0.001) and to metoprolol succinate (80.1 ± 8.1 bpm; p < 0.001), a significantly lower NT-proBNP level (588.4 ± 461.4 pg/mL) compared to baseline (3849.7 ± 1960.0 pg/mL; p < 0.001) and to metoprolol succinate (1229.0 ± 1098.6 pg/mL; p = 0.005), a significantly lower overall mortality (20.4% versus 46.4%; p = 0.004), and mortality due to graft failure (1.9% versus 21.4%; p = 0.001). Multivariate analysis showed a significantly decreased risk of death within 10 years after HTX in patients with post-transplant use of ivabradine (HR 0.374, CI 0.182–0.770; p = 0.008). Conclusions: In this single-center trial, patients with ivabradine revealed a significantly more pronounced heart rate reduction, a lower NT-proBNP level, and a superior 10-year survival after HTX.